2022
DOI: 10.11622/smedj.2020117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of anti-DFS70 for identifying antinuclear antibody-positive patients without systemic autoimmune rheumatic disease

Abstract: INTRODUCTION The antinuclear antibody (ANA) test is a screening test for systemic autoimmune rheumatic disease (SARD). We hypothesised that the presence of anti-DFS70 in ANA-positive samples was associated with a false-positive ANA test and negatively associated with SARD. METHODS A retrospective analysis of patient samples received for ANA testing from 1 January 2016 to 30 June 2016 was performed. Patient samples underwent ANA testing via indirect immunofluorescence method and anti-DFS70 testing using enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It was consistent with our recent study, which suggested that anti-DFS70 antibodies were associated with anti-dsDNA antibodies in lupus nephritis (LN) patients ( 15 ). In addition, our findings also agree with one recent study on anti-DFS70 antibodies that showed that all eight anti-DFS70-positive patients with SARD were Chinese and 75% (6/8) of them had anti-dsDNA antibodies as well ( 25 ). It indicated a potential relationship of anti-DFS70 antibodies with anti-dsDNA in Chinese SLE patients.…”
Section: Discussionsupporting
confidence: 92%
“…It was consistent with our recent study, which suggested that anti-DFS70 antibodies were associated with anti-dsDNA antibodies in lupus nephritis (LN) patients ( 15 ). In addition, our findings also agree with one recent study on anti-DFS70 antibodies that showed that all eight anti-DFS70-positive patients with SARD were Chinese and 75% (6/8) of them had anti-dsDNA antibodies as well ( 25 ). It indicated a potential relationship of anti-DFS70 antibodies with anti-dsDNA in Chinese SLE patients.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we also found that different definitions of SARD may influence the diagnostic performance of anti-DFS70 antibodies. In the literature, the term SARD describes autoimmune disorders affecting multiple organs, such as SLE, systemic sclerosis, rheumatoid arthritis and systemic vasculitis [ 31 , 36 , 39 ]. However, a positive ANA test is only essential in the diagnosis of some disorders included in SARD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the reference standard, only one of the studies applied the classification criteria of SARD [2]. Due to possible heterogeneity in the clinical diagnosis and practice, the studies using reference standards other than classification criteria were assessed as having an unclear risk of bias and applicability in the reference standard [30][31][32][33][34][35][36]. For flow and timing, because none of the enrolled studies specified the time interval between the index test and the diagnosis of SARD, the appropriateness of the interval between the index test (anti-DFS70 antibodies) and the reference standard (the diagnosis of SARD) could not be assessed.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…11,[13][14][15][16][17] Recent studies have cast doubt on the performance of anti-DFS70 antibodies for excluding AARD. 16,[18][19][20][21][22] The prevalence of anti-DFS70 antibodies in AARD varies in different studies. 16 , 23-25 A meta-analysis found that in patients with positive ANA test results, the pooled specificity of using anti-DFS70 antibodies to exclude AARD was 98%, but the pooled sensitivity was only 18%.…”
Section: Introductionmentioning
confidence: 99%